A DEFENSE OF BUDDHISM, MEDITATION, AND FREE WILL: A THEORY OF MENTAL FREEDOM: with Christian Coseru, "Free Your Mind: Buddhist Meditation and the Free Will Problem"; Gregg D. Caruso, "Buddhism, Free Will, and Punishment: Taking Buddhist Ethics Seriously"; David Cummiskey, "Ego‐less Agency: Dharma‐Responsiveness without Kantian Autonomy"; Karin L. Meyers, "Mental Freedom and Freedom of the Loving Heart: Free Will and Buddhist Meditation"; and Rick Repetti, "A Defense of Buddhism, Meditation, and Free Will: A Theory of Mental Freedom.". Issue 2 (11th June 2020) - Repetti, Rick
Abstract: This is my response to the criticisms of Gregg Caruso, David Cummiskey, and Karin Meyers, in their roles as members of the "Author Meets Critics" panel devoted to my book, Buddhism, Meditation, and Free Will: A Theory of Mental Freedom at the 2019 annual meeting of the Eastern Division of the American Philosophical Association, organized by Christian Coseru. Caruso's main objection is that I am not sufficiently attentive to details of opposing arguments in Western philosophy, and Cummiskey's and Meyers' objections, similarly, are that I am insufficiently attentive to details of Buddhism. I argue that all such objections, however putatively correct, do not rise to the level of objections that actually undermine my account of mental freedom.